Microbial community succession characteristics in an anaerobic baffled reactor during phenol gradient acclimation - Yuan LI; Chunmei YU; Daqiang CANG (工程科学学报)
Anaerobic digestion (AD) is extensively used for treating both industrial and municipal wastewater owing to its cost-efficiency and eco-friendly nature. However, phenol in polluted effluents can destabilize AD performance. To increase phenol tolerance to AD microbial communities, stepwise acclimatization is commonly employed. This method also aids in selecting microorganisms well-suited for phenol degradation. In this study, anaerobic sludge acclimatization was conducted using a four-chamber anaerobic bafﬂed reactor (ABR). Initially, the reactor was fed with glucose as the sole carbon source. Phenol levels in the influent increased stepwise from 100 to 300 mg·L−1. In the final experimental phase, the reactor processed wastewater containing 780 mg·L−1 of phenol as the sole substrate, without glucose. We analyzed hydrogen partial pressure, pH, chemical oxygen demand (COD), and phenol concentration to examine changes in reactor performance. The Microbial community dynamics were investigated using Illumina high-throughput sequencing technology. Phenol degradation intermediates were performed using gas chromatography/mass spectrometry (GC–MS), with their quantities measured by high-performance liquid chromatography. The results showed a decrease in hydrogen partial pressure from 5 to 20 Pa in the ABR from Chamber 1 to Chamber 4. The pH levels in the first chamber fluctuated from 5.0 to 6.8 with glucose alone and increased with phenol addition. Nearly 90% of COD and phenol were degraded in the initial two chambers. However, COD levels remained at 100 mg·L−1 in the last two chambers, suggesting the presence of nondegradable components in the effluent. α-diversity analysis indicated Shannon, Simpson, and Chao1 indices for bacterial and archaeal communities with glucose and phenol as carbon sources in the feed. Acclimatization significantly altered the microbial community structure, shifting dominant families from Streptococcaceae and Enterobacteriaceae to Syntrophaceae, and archaeal families from Methanobacteriaceae to Woesearchaeales. Redundancy analysis (RDA)linked Syntrophaceae and Woesearchaeales to phenol degradation and acetotrophic processes, respectively. GC–MS analysis revealed propionic acid as the only effluent component. The randomized methyl–malonyl–CoA pathway and the C-6-dismutation pathway are two known routes for propionate degradation. However, the ΔG' values for these reactions were consistently greater than −20 kJ·mol−1, indicating that propionate degradation did not occur under the experimental conditions. From a thermodynamic point of view, high hydrogen partial pressure levels in the reactor affected the propionate degradation process and also inhibited sludge bioactivity. Syntrophobacter and Smithella are responsible for degrading propionate. The relative abundance of these two families slowly increased from 0.35% to 6.9% in the ABR from Chamber 1 to Chamber 4. These findings account for the inadequate efficiency of COD removal observed in the effluent.